ANALISIS EFISIENSI USAHATANI IKAN MAS DALAM KARAMBA DI KELURAHAN PAHANDUT SEBERANG KECAMATAN PAHANDUT KOTA PALANGKA RAYA - Selpi, Selpi; Pordamantra, Pordamantra; Yuprin, A. D. (Program Studi Agribisnis Jurusan Sosial Ekonomi Pertanian Fakultas Pertanian Universitas Palangka Raya, 2018)
The research was conducted to analyze the income of common carp farming in karamba, analyze the factors that affect the production of carp in karamba and analziying the efficiency of the production factors of the common carp in the cages in the village of Pahandut Seberang. The research was conducted in the Pahandut Seberang Village, site selection is determined purposively. Sampling method in this research is simple random sampling, where samples taken as many as 35 samples. The results showed that total cost incurred is Rp 36.916.093, the revenue is Rp 85.659.510. Furthermore, the income of goldfish farmers in karamba is Rp 48.743.417 per one time production. R/C analysis is 2,31 meaning that carp farming in karamba in Pahandut Seberang village is profitable and feasible to cultivate. The results of the analysis show the value of adj R2 = 0,928 and the value of F arithmetic of 88,754 with sig 0,000. Factors that significantly affect the production goldfish of deep carp karamba is labor (X1), volume karamba (X2) number of seed (X3), number of feed (X4) and medicine (X5). The results of the efficiency of the allocative afficiency of the factors of production of carp farming in the cage is NPMx/Px for labor is fish farming goldfish in the cage is of 3,84 > 1 so that not yet efficiency, NPMx/Px for karamba volume that is equal to 3,31 > 1 so that not yet efficiency, NPMx/Px for the amount of seed that is equal to 1,51 > 1 so that not yet efficiency, NPMx/Px amount of feed that is equal to 0,74 < 1 so that has not efficient, NPMx/Px drugs that is equal to 5,43 > 1 so not yet efficiency.